Myoglobin Immunoassay Utilizing Directional Surface Plasmon-Coupled Emission - Matveeva, Evgenia (Anal Chem, 2004)
We described an immunoassay for the cardiac marker myoglobin on a thin silver mirror surface using surface plasmon-coupled emission (SPCE). SPCE occurs for fluorophores in proximity (within ~200 nm) of a thin metal film (in our case, silver) and results in a highly directional radiation through a glass substrate at a well-defined angle from the normal axis. We used the effect of SPCE to develop a myoglobin immunoassay on the silver mirror surface deposited on a glass substrate. Binding of the labeled anti-myoglobin antibodies led to the enhanced fluorescence emission at a specific angle of 72°. The directional and enhanced directional fluorescence emission enables detection of myoglobin over a wide range of concentrations from subnormal to the elevated level of this cardiac marker. Utilizing SPCE allowed us also to demonstrate significant background suppression (from serum or whole blood) in the myoglobin immunoassay. We expect SPCE to become a powerful technique for performing immunoassays for many biomarkers in surface-bound assays.